After-School Behaviors, Self-Management, and Parental Involvement as Predictors of Academic Achievement in Adolescents - Meng Xiao; Mingzhang Zuo; Xinqi Liu; Kunyu Wang; Heng Luo (Behavioral Sciences, 2025)
How adolescents’ after-school behaviors, self-management, and parental involvement are associated with their academic success and personal development has drawn growing attention. This study systematically examined how these three factors predict academic achievement. Data were collected from 353 seventh-grade students through a self-designed daily behavior log sheet and self-management app, and multiple linear regression analysis was conducted to identify key predictors. The results indicated that academic achievement was positively related to sleep quality, homework duration, self-assessment, and parental involvement, while it was negatively associated with sleep duration, exercise duration, and the number of daily planned tasks. Despite these insights, the study has limitations, including reliance on self-reported data, which may introduce bias, and the use of a cross-sectional design, which precludes determining the temporal sequence of variables and inferring causal relationships. These findings provide valuable insights for educators, parents, and students; they also emphasize the importance of organizing students’ after-school activities effectively, enhancing their self-management competencies, and encouraging active parental involvement in fostering students’ academic success and overall development.